Defining a relationship between pearlite morphology and ferrite crystallographic orientation. (1st May 2017) - Durgaprasad, A.; Giri, S.; Lenka, S.; Kundu, S.; Mishra, S.; Chandra, S.; Doherty, R.D.; Samajdar, I.
Abstract: This study involved fully pearlitic wires of seven different diameters (5.5–1.6 mm). All samples were laboratory annealed to re-austenitize and were then air-cooled to reform the pearlite structure. Morphological alignment of the pearlite, along the wire axis, improved significantly, 32% to 93%, as the wire diameter decreased. This improvement coincided with increases in the <110> ferrite fiber texture, and falls in the axial residual stresses. In all the wires, the majority of the pearlite lamellae appeared to align, in a 2-D analysis, with minimum elastic stiffness (EMin under simple compression) for the ferrite (α). This correlation increased from 80% to 98% with decrease in wire diameter and fall in axial residual stresses. 3-D microstructures by serial sectioning, 3-D rotations seeking EMin and observations on coarse pearlite, indicated that 011α and <001> α were, respectively, the pearlite interface (or habit plane) and growth direction. Graphical abstract: Image 1